A handbook for construction planning and scheduling - Bordoli, David; Baldwin, Andrew 1950- (John Wiley & Sons Ltd., 2014)
This handbook acts as a guide to good practice, a text to accompany learning and a reference document for those needing information on background, best practice, and methods for practical application.